Lactulose reduces bacterial DNA translocation, which worsens neurocognitive shape in cirrhotic patients with minimal hepatic encephalopathy. (29th July 2016) - Moratalla, Alba; Ampuero, Javier; Bellot, Pablo; Gallego‐Durán, Rocío; Zapater, Pedro; Roger, Manuela; Figueruela, Blanca; Martínez‐Moreno, Belén; González‐Navajas, José M.; Such, José; Romero‐Gómez, Manuel; Francés, Rubén
Abstract: Background & Aims: Minimal hepatic encephalopathy is associated with poor prognosis and mortality in patients with cirrhosis. We aimed at investigating whether bacterial‐DNA translocation affects hyperammonaemia and neurocognitive scores in patients with mHE according to the use of lactulose. Methods: Observational study including 72 mHE cirrhotic patients, as defined by a psychometric hepatic encephalopathy score (PHES)<−4 and/or a critical flicker frequency (CFF)<39 Hz. Bacterial‐DNA, serum ammonia, pro‐inflammatory cytokines and nitric oxide levels were evaluated. A second cohort of 40 lactulose‐untreated patients were evaluated before and 6–month after lactulose administration (30–60 mL/d). Results: In the first cohort, bacterial‐DNA rate was significantly higher in patients without lactulose (39% vs 23%, P =.03). Serum ammonia and inflammatory markers were significantly increased in patients with bacterial‐DNA, regardless the use of lactulose, and correlated with the amount of amplified bacterial‐DNA. Neurocognitive scores were significantly worse in bacterial‐DNA positive vs negative patients (PHES −7.6±1.1 vs −5.5±1.0; CFF 32.5±2.6 vs 36.2±2.8, P =.01). Lactulose was associated with improved neurocognitive scores in patients without bacterial‐DNA. Serum ammonia levels inversely correlated with neurocognitive scores in patients with bacterial‐DNA (PHES r=−.84; CFF r=−.72, P =.001). In the second cohort, lactulose reduced bacterial‐DNA translocation (36%–16%, P =.02). Neurocognitive scores were significantly improved in bacterial‐DNA positive patients who cleared bacterial‐DNA during the period on lactulose. Serum ammonia levels correlated with both neurocognitive scores in patients with bacterial‐DNA, either before or after lactulose. Conclusion: Bacterial‐DNA translocation worsens neurocognitive scores in mHE patients and it is reduced by lactulose, enhancing the relevance of controlling bacterial antigen translocation in these patients.